Mathematical model for strategic planning optimization in the pome fruit industry - Catala, Luis Pedro (2013)
This paper presents a strategic planning model for optimal restructuring of a pome (pears and apples) production farm concerning varieties and planting densities. The model decides the optimal investment policy for a given farm, maximizing the net present value of business while dynamically deciding its planting structure along a given time horizon under different financing scenarios. The model constraints impose restrictions on the activities to take into account risks and cultural practices. The mathematical model corresponds to a mixed integer linear programming problem, where integer decisions are related to the minimum reconversion land unit and funding requirements. The model was applied to a realistic case study of a typical farm in the ‘‘Alto Valle de Río Negro’’ Argen- tine region. The study was conducted over a 20-year time horizon considering four varieties of apples and five of pears. The results showed the optimal investment policy for the replacement of varieties under different scenarios, with and without external financing. A sensitivity analysis was also performed on some of the most influential parameters. The model could be used either by governmental agencies to advise private sectors and to develop strategic economic policies or by companies to optimize the busi- ness profit.